MICROELEMENT IMBALANCES IN INTESTINAL HELMINTHIASIS (ZAMONAVIY TARAQQIYOT VA FAN: 21-ASR YONDASHUVLARI, 2025)
Helminths compete with the host for essential micronutrients such as iron, zinc, copper, selenium, and magnesium, and may also impair their absorption in the intestine. Microelement deficiencies contribute to anemia, growth retardation, cognitive impairment, and reduced resistance to infections. Despite the clinical importance of these disturbances, microelement imbalances in intestinal helminthiasis remain insufficiently studied, and approaches to their correction are not standardized.